(3JQLeI GdSdWGf SdjeGf Hf Sdje GdYKeGfis - (3bWH GdOjf SdjeGf NGf Hf Sdje NGf Hf HGjRjO NGfs
(3ChdgG (B:s
(3PcQ JQLeI GdSdWGf GdCYXe efbhd ef eShOI ehdGfG bWH GdOjf SdjeGf NGf Hf Sdje NGf Hf HGjRjO NGf gPG MbjbI fSHI GdcQje s
(3BNQgG (B:s
(3hMSGe HGTG hgeOe HGTG HccQJci GfJgi , gPG eG hLOJg HNWg QMeg Gddg , hGdMeOddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B993s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs